Violation of the procedure for international transfers of goods subject to state export control: problems of determining the moment of termination - Gorbachov, D. M. (Аналітично-порівняльне правознавство, 2025)
The article establishes that determination of the moment of termination of a violation of the procedure for international transfers of goods subject to state export control may be established by interpreting the elements of this criminal offense, which are blanket and require clarification of the relevant provisions in the regulatory legislation of Ukraine. In addition, when establishing the moment of termination of the criminal offense under Article 333 of the Criminal Code of Ukraine, it is necessary to proceed from the fact that the socially dangerous act in this article is referred to as “violation of the procedure for international transfer of goods”, and not as their transfer. Violation of the procedure for the international transfer of goods subject to state export control, if the accused physically attempts to cross the state (customs) border of Ukraine by carrying or transporting the said goods, should be considered a completed criminal offense not from the moment the guilty person crosses the state (customs) border, but from the moment the accused attempted to cross the state (customs) border of Ukraine with goods subject to state export control. If the accused moves goods subject to state export control by sending them by mail, the act is considered completed from the moment the parcel is processed and sent, regardless of whether the addressee has received them and regardless of whether the parcel has crossed the state (customs) border of Ukraine. The same applies to the shipment of goods subject to state export control in the form of baggage or by courier. It is from the moment the relevant documentation is executed that the criminal offense under Art. 333 of the Criminal Code of Ukraine is considered complete, since the person has already violated the rules of international transfers of goods by sending or transferring goods subject to state export control. In particular, the person did so without registration in accordance with the procedure provided for by the legislation of Ukraine, without the appropriate permission or conclusion of the State Export Control Service.